Morphology and histochemistry of the hyolingual apparatus in chameleons - Boleli, Isabel Cristina [UNESP]; Bitondi, Marcia Maria Gentile; Figueiredo, Vera Lucia Castelo; Simoes, Zila Luz Paulino (Wiley, 2001)
We reexamined the morphological and functional properties of the hyoid, the tongue pad, and hyolingual musculature in chameleons. Dissections and histological sections indicated the presence of five distinctly individualized pairs of intrinsic tongue muscles. An analysis of the histochemical properties of the system revealed only two fiber types in the hyolingual muscles: fast glycolytic and fast oxidative glycolytic fibers. In accordance with this observation, motor-endplate staining showed that all endplates are of the en-plaque type. All muscles show relatively short fibers and large numbers of motor endplates, indicating a large potential for fine muscular control. The connective tissue sheet surrounding the entoglossal process contains elastin fibers at its periphery, allowing for elastic recoil of the hyolingual system after prey capture. The connective tissue sheets surrounding the m. accelerator and m. hyoglossus were examined under polarized light. The collagen fibers in the accelerator epimysium are configured in a crossed helical array that will facilitate limited muscle elongation. The microstructure of the tongue pad as revealed by SEM showed decreased adhesive properties, indicating a change in the prey prehension mechanics in chameleons compared to agamid or iguanid lizards. These findings provide the basis for further experimental analysis of the hyolingual system. © 2001 Wiley-Liss, Inc.
Keywords: Chameleonidae; Functional morphology; Histochemistry; Morphology; Motor-endplate staining; acetylcholinesterase; adenosine triphosphatase; succinate dehydrogenase; animal; comparative study; connective tissue; cytochemistry; cytology; enzymology; feeding behavior; histology; hyoid bone; innervation; lizard; metabolism; movement (physiology); muscle cell; neuromuscular synapse; physiology; scanning electron microscopy; skeletal muscle; taste bud; tongue; ultrastructure; Acetylcholinesterase; Adenosine Triphosphatases; Animals; Connective Tissue; Feeding Behavior; Histocytochemistry; Hyoid Bone; Lizards; Microscopy, Electron, Scanning; Movement; Muscle Fibers; Muscle, Skeletal; Neuromuscular Junction; Succinate Dehydrogenase; Taste Buds; Tongue; Agamidae; Chamaeleonidae; Iguanidae; Squamata